Food bolus‐forming ability predicts incidence of aspiration pneumonia in nursing home older adults: A prospective observational study. (26th August 2019) - Hase, Takashi; Miura, Yuka; Nakagami, Gojiro; Okamoto, Shigefumi; Sanada, Hiromi; Sugama, Junko
Abstract: Background: Food boluses in the pharynx without enough bolus formation sometimes cause aspiration among older adults; however, the relationship between food bolus‐forming ability and incidence of aspiration pneumonia is unclear. Objective: To investigate the relationship between food bolus‐forming ability and incidence of aspiration pneumonia by evaluating the condition of chew‐swallow managing food transported into the pharynx. Methods: A prospective observational study conducted in a nursing home for the elderly between April 2016 and February 2018. Seventy‐three residents who swallowed thickened liquids and consistent boluses without aspiration were included. Food boluses were graded into three categories in the pharynx using videoendoscopic evaluation. Boluses that retained their original shape were defined as Grade 1. A mixture of large and small boluses was defined as Grade 2. Boluses that had completely transformed into a paste were defined as Grade 3. The relationship between the bolus formation grade and incidence of aspiration pneumonia over 6‐month follow‐up was investigated. Results: Seventeen residents developed aspiration pneumonia. The incidence rate of aspiration pneumonia was highest among residents with Grade 1 boluses, at an incidence rate of .187 cases per person‐month (95% confidence interval (CI): 0.097‐0.359). Cox regression showed residents with Grade 1 boluses had a hazard ratio of 4.548 (1.393‐14.85) for incidence of aspiration pneumonia compared with residents who had Grade 2 or 3 boluses. Conclusion: Insufficient food bolus‐forming ability predicted high incidence of aspiration pneumonia. Healthcare professionals should evaluate the food bolus‐forming ability, as well as swallowing function, to prevent aspiration pneumonia.